The Role of Machine Learning in Modern Software Development - Misri, Mustafa Eisa (Westscience Press, 2025)
The integration of machine learning (ML) into software applications is increasingly essential for enhancing functionality, decision-making, and performance in diverse fields. As industries strive to leverage intelligent systems, ML enables software to adapt dynamically, process large datasets efficiently, and deliver insights with minimal human intervention. This paper investigates the methodology of incorporating machine learning models into software systems, focusing on model selection, training, optimization, and real-time deployment. We present case studies on fraud detection systems and embedded applications, highlighting challenges, optimization techniques, and the role of continuous learning in maintaining model accuracy. Furthermore, the importance of explainable machine learning models for fostering user trust and understanding is emphasized. With the advent of technologies like Machine language operations and federated learning, ML is becoming more accessible and scalable, even in resource-constrained environments. This paper concludes with discussions on the advantages and limitations of ML integration and future directions in enhancing model performance, scalability, and privacy-preserving capabilities.